Direct Fabrication of 3D Metallic Networks and Their Performance. Issue 7 (12th December 2016) - Ron, Racheli; Gachet, David; Rechav, Katya; Salomon, Adi
Abstract : Fabrication of macroscopic nanoporous metallic networks is challenging, because it demands fine structures at the nanoscale over a large‐scale. A technique to form pure scalable networks is introduced. The networked‐metals ("Netals") exhibit a strong interaction with light and indicate a large fraction of hot‐electrons generation. These hot‐electrons are available to derive photocatalytic processes.